Tanggapan Siswa Terhadap Kompetensi Profesional Guru Hubungnnya dengan Prestasi Kognitif Mereka Pada Mata Pelajaran PAI - Ila Nurfitriah; Jamaluddin (Gunung Djati Conference Series, 2022)
This study aims to determine student responses to professional teacher competence in relation to their cognitive achievement in PAI subjects at SMPN 1 Cianjur. This study uses a descriptive method with a quantitative approach and ex-postfacto research model, the data collection is literature study, questionnaires, tests, documentation studies. And data analysis using a statistical approach, namely: partial analysis, data normality test and correlation test, the research sample was 80 students of class VIII SMPN 1 Cianjur. So the results of the study can be seen (1) student responses to teacher professional competence (variable X) in the high category with a number of 4.01 which is in the range (3.15 -4.50); (2) their cognitive achievement in PAI subjects (Variable Y) is in the good category with a score of 75.3 which is in the range (70-79); (3) the relationship between the two variables is 0.19, while the effect of the variable (X) on the variable (Y) is 3%. Thus there are still 97% of other factors that affect their learning cognitive achievement. Therefore, it can be said that students' responses to the competence of PAI teachers are quite good, this can be seen from the competence of qualified PAI teachers to become professional teachers, and is evidenced by the motivation of students to follow their learning. However, most of the students' cognitive achievement is still low, this can be seen from most of the students' cognitive achievements that have not reached the KKM score.